2011
DOI: 10.1002/arp.421
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Toolkit for the Visualization of Archaeological Features on Airborne LiDAR Elevation Data

Abstract: A range of techniques have become established for the visualization and analysis of airborne LiDAR elevation data within the field of archaeology. In this paper we discuss the visualization of test data representing archaeological features in a variety of terrains using a suite of techniques, all available through generic geographical information system or image processing software. These comprise elevation shading using constrained colour ramps, slope analysis, hillshading, principal component analysis of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
3
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 16 publications
2
72
3
7
Order By: Relevance
“…It also confirms on a fully analytical basis that this combination should be based mainly on DEM-manipulating methods such as SLOPEVIS and LRM [35,46]. This is supported by the fact that, for any dataset with a natural distribution of slopes and curvatures, they will always provide more contrast.…”
Section: A Detailed Assessment Of Als-derived Raster Visualization Tementioning
confidence: 54%
“…It also confirms on a fully analytical basis that this combination should be based mainly on DEM-manipulating methods such as SLOPEVIS and LRM [35,46]. This is supported by the fact that, for any dataset with a natural distribution of slopes and curvatures, they will always provide more contrast.…”
Section: A Detailed Assessment Of Als-derived Raster Visualization Tementioning
confidence: 54%
“…While in positive openness (Figure 8a) only nine barrows are visible, according to the interpretation of the LRM the area is covered by at least fifteen burials (Figure 8b,c). This is a clear advantage of LRM over any other known technique and demonstrates the importance of combining various visualizations, since all of them filter and display information content in a different way (see also [9] and [10]; p. 47).…”
Section: Openness Compared To Local Relief Modelmentioning
confidence: 99%
“…Kokalj et al discuss various techniques, including hillshades and derivatives, techniques of elevation differentiations, LRM, SVF, PCA, and various composites [8]. Keith Challis et al [9] published an assessment of visualization techniques and proposed a "toolbox" for low and high relief landscapes, which includes elevation shading, slope severity, solar insolation models and LRM. Another comparison of these techniques was made by Bennett et al [10].…”
Section: Open Accessmentioning
confidence: 99%
“…Some applications of solar isolation [45] showed that their results are more efficient because the illumination source (the Sun) moves. This movement partially removes the issue of direct illumination.…”
Section: Figurementioning
confidence: 99%